2018
DOI: 10.3390/jof4030100
|View full text |Cite
|
Sign up to set email alerts
|

Immunity and Treatment of Sporotrichosis

Abstract: Species of the Sporothrix complex are the etiological agents of sporotrichosis, an important subcutaneous mycosis with several clinical forms and an increasing incidence around the world that affects humans and other mammals. The immunological mechanisms involved in the prevention and control of this mycosis are not entirely understood. Many reports have suggested that cell-mediated immunity has an essential role in the development of the disease, being the primary response controlling it, while only recent da… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
44
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(57 citation statements)
references
References 88 publications
0
44
0
Order By: Relevance
“…Previous studies have suggested that T cell-mediated immunity plays an essential role in the immunity against infection with S. schenckii and S. brasiliensis (19). To make clear T cells' profile in S. globosa infection in human, effector CD4 + T (Teff) cells were evaluated in SP (patients with sporotrichosis) and HC ( Figures 1, S1).…”
Section: Th2 and Th17 Inclined Responses In Peripheral Blood Of Sporomentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies have suggested that T cell-mediated immunity plays an essential role in the immunity against infection with S. schenckii and S. brasiliensis (19). To make clear T cells' profile in S. globosa infection in human, effector CD4 + T (Teff) cells were evaluated in SP (patients with sporotrichosis) and HC ( Figures 1, S1).…”
Section: Th2 and Th17 Inclined Responses In Peripheral Blood Of Sporomentioning
confidence: 99%
“…In addition to cellular immunity, humoral response in experimental sporotrichosis in mice has also been evaluated (19). IgG antibodies against Sporothrix antigens could be detected throughout the infection in mice (20).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The pulmonary (extracutaneous) form manifests itself through the inhalation of conidia, usually related to immunodeficiency [10]. The severity of the clinical forms of sporotrichosis depends on the site of inoculation, depth of infection, the virulence of the fungal strain, and the patient's immune status [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…The antifungal repertoire to treat sporotrichosis usually depends on the clinical form of the disease, the longevity of the infection, the presence of other chronic illnesses in the patient, and the fungal species. Terbinafine, potassium iodine, and some azoles are among the drugs with good antifungal activity against Sporothrix spp., as discussed here by García-Carnero et al [16]. Due to the limited options currently available to treat sporotrichosis and the constant menace of acquisition of antifungal drug resistance, the generation of passive and active immunological approaches has emerged as a new research area to control fungal infections, including sporotrichosis.…”
mentioning
confidence: 99%